A MODERN VIEW ON THE THERMOLISIS OF HYDRATE ZINC-MANGANESE(II) PHOSPHATES - Antraptseva, Nadezhda; Voloshchuk, Solomiya; Zhitnetskyi, Ihor; Bila, Galina (SWorld-Ger Conference proceedings, 2023)
The work was carried out in order to study the modern view on the thermolysis of zinc-manganese(II) phosphate tetrahydrates of the general formula Zn3-xMnx(PO4)2•4H2O Using the example of phosphate with the composition Zn2Mn(РO4)2·4Н2O, it was